Results of Experimental Studies of the Seed Drill for Row Sowing SZD4.0 - S. I. Kambulov; G. G. Parkhomenko; I. V. Bozhko; A. A. Boyko (Сельскохозяйственные машины и технологии)
Sowing units are considered to be the most complex agricultural machines, as they perform many operations - both sequentially and simultaneously. At the same time, agricultural producers are interested in the high-quality operation of the units. For the high-quality execution of technological operations and the improvement of energy indicators, seeders it is important to know and improve their design.(Research purpose) To determine the main agrotechnical and energy indicators of the seed drill for row sowing of SZD-4.0.(Materials and methods) Experimental studies of the SZD-4.0 seed drill were carried out on winter wheat sowing at a soil moisture content of 8.4-29.7 percent in a layer of 5-10 centimeters, a soil hardness of 0.8-2.0 megapascals, the depth of a loosened layer fractions of 0-10 centimeters amounted to 48.0-53.2 percent. Energy assessment was carried out at three speed modes in an aggregate with an MTZ-80 tractor equipped with a dynamometer and a measuring recording system.(Results and discussion) The main agrotechnical indicators of the seeder were revealed: the average depth of seed placement at the maximum, minimum and optimal depth of the coulters, the quantitative proportion of seeds planted at a specified depth, the height of the ridges after the passage of the unit, the number of seedlings and relative field germination. The authors studied the main energy indicators: the traction resistance of the seeder, the power consumption of the unit, the power spent on overcoming the traction resistance of the machine, the specific energy consumption of the unit, the specific fuel consumption during the main operation, the specific traction resistance.(Conclusions) It was confirmed that when the speed of the unit was 9.5-13.5 kilometers per hour, the working bodies of the seeder provided the depth of seed placement, the actual seeding rate, and the quantitative proportion of seeds planted in the layer corresponding to agricultural requirements. They determined the optimal mode of operation: at a speed of 12.04 kilometers per hour, with a coulter depth of 54.6 millimeters and when loading the engine of an energy facility by 76 percent.